PROTOTYPE SISTEM MONITORING, DETEKSI KEBAKARAN DAN NOTIFIKASI BERBASIS IoT (Internet of Things) - Irfan; Akhlis Munazilin; Abdul Ghofur (Journal of Innovation Research and Knowledge, 2024)
: Fire is a situation where a building in a place such as a house/settlement, factory, market, building and so on is being hit by fire which causes casualties and/or losses, therefore fire is categorized as a disaster. There were 17,768 fire cases that occurred in Indonesia throughout 2021, of which 5,274 were caused by electrical short circuits or around 45%. The source of the fire itself is an electrical short circuit (70% of residential fires), gas cylinder/gas stove leaks, cigarette butts, and hot weather. From several previous studies, the system/equipment created was indoors and would only focus on certain houses/buildings. The difference that researchers made was using the Smart Village concept. Halim Iskandar defines Smart Village as village development based on the application of appropriate technology. By implementing this technology, it is hoped that villages can achieve various breakthrough achievements so that they meet the qualifications to enter the independent village category. Therefore, an outdoor system is needed to monitor, detect and provide warnings before a fire grows, so that the community works together to extinguish the fire while waiting for the fire brigade to arrive.